Nasionalisme, Negara-Bangsa, dan Integrasi Nasional Indonesia: Masih Perlukah? - Singgih Tri Sulistiyono (Department of History, Faculty of Humanities, Diponegoro University, 2018)
This article based on small and trivial statements but actually has a very basic content that is often raised by some of the younger generations about the lack of importance of nationalism, nation-state and national integration of Indonesia. Perhaps such a statement is a reflection of the mood of thinking and taste of the young generation who are the mile-generation immersed in the euphoria of globalization and the advances in technology and communications and information that make the world like a village, often referred to as a 'global village'. Depart from that reality, this article aims to reflect the understanding of nationalism, nation-state, and national integration, utilizing previous studies conducted by the experts.